AKTIVITAS ENZIM SELULASE, AMILASE, DAN INVERTASE PADA TANAH PERTANIAN DARI DUSUN KRANGKENG, JAWA TENGAH - Sherly Asnath Saukoly (Scripta Biologica, 2019)
Cellulase, amylase and invertase enzymes are included in the hydrolysis enzime group which plays the role in the transformation and decomposition of organic material, biochemical reaction and nutrients cycle in the ground. There is limited information about the influence of plants above the ground toward the activities of those three enzymes in Indonesia. The activities of those three enzymes have been examined on the farmland with tomatoes (Solanum lycopersicum), chicory (Brassica rapa subsp. pekinensis), chili (Capsicum annum), and leek (Allium fistulosum). This study shows that there is an influence of plants above the ground toward the activities of celluloid and invertase enzymes (below ground) (p0,05). Besides, there is a positive correlation between the enzymes activities and the abiotic factors such as ground organic material, pH and soil moisture (p